Evidence of No Association Between Human Papillomavirus and Breast Cancer - Bønløkke, Sara; Blaakær, Jan; Steiniche, Torben; Høgdall, Estrid; Jensen, Steffen Grann; Hammer, Anne; Balslev, Eva; Strube, Mikael Lenz; Knakkergaard, Helle; Lenz, Suzan (Frontiers in Oncology, 2018)
Background. Globally, breast cancer is the most frequent cancer among women. Studies reported an increased risk of breast cancer among women with prior cervical dysplasia. This study aimed to describe the prevalence of human papillomavirus (HPV) in breast cancer and explore if women with prior cervical neoplasia carry an increased risk of HPV positive breast cancer compared to women without. Methods. This case-control study identified 193 Danish women diagnosed with breast cancer (1998-2012) at Aarhus University Hospital or Copenhagen University Hospital Herlev. Cases were 93 women with cervical intraepithelial neoplasia grade 3 or worse (CIN3+) prior to breast cancer. Controls were 100 women without prior cervical dysplasia. HPV testing and genotyping was done using SPF10 PCR-DEIA-LiPA25 and an in-house semi-Q-PCR assay. Results. Overall HPV prevalence in breast cancer for the assays was 1.55% (95% CI 0.32 – 4.48) and 0.52% (95% CI 0.01 – 2.85), respectively. There was no difference in HPV prevalence between cases and controls (2.15% vs. 1.00%, p=0.61 and 1.08% vs. 0.00%, p=0.48). HPV prevalence in CIN3+ was 94.62% (95% CI 0.88 – 0.98). Concordance between the assays was 98.60%. Conclusion. HPV prevalence in breast cancer is very low suggesting no etiological correlation between HPV and breast cancer.